Utilizing Water Hyacinth (Eichhornia crassipes) from Srandakan Bantul, Indonesia for ‘Bright Fever Patch’ as an Alternative Children’s Fever Therapy - Niswara, Anggita Kamalia; Kusrinanti, Nabillah Ainun; Firdaus, Rizqi Amalia; Ikhsanudin, Azis (UI Scholars Hub, 2024)
In 2022, Indonesia experienced a public health crisis involving acute kidney failure in children, traced to paracetamol syrup contaminated with ethylene glycol and diethylene glycol. This underscores the urgent need for safer antipyretic alternatives. This study investigates the antipyretic potential of transdermal patches formulated with ethanol extract of water hyacinth (Eichhornia crassipes) leaves sourced from Srandakan, Bantul, Yogyakarta. Extract concentrations of 0.8%, 1.0%, and 1.2% were tested, alongside a negative control (no extract) and a positive control (paracetamol). The patches underwent evaluations for organoleptic properties, weight uniformity (0.41±0.02 to 0.52±0.02 g), thickness (0.36±0.03 to 0.41±0.03 mm), water absorption (5.95%±0.04 to 17.45%±0.04), folding endurance (all >300 times), and pH (4.05±0.03 to 4.20±0.04). Antipyretic activity was assessed in vivo using Wistar rats. The 1.2% extract patch (F3) showed a temperature reduction of 57.45±14.31% at 180 minutes, while paracetamol achieved 74.07±11.38%. Although paracetamol showed greater efficacy, the extract patch acted faster. Both paracetamol and extract patch were statistically significant compared to placebo (p<0.001). Although paracetamol exhibited a stronger antipyretic effect than the extract patch, this difference was not statistically significant (p=0.847). These findings support the further development of the water hyacinth extract patch as a promising antipyretic alternative, with potential improvements through the enhancement of the formulation and the development of a slow-release system.